Protective role of Pannexin1 in lymphatic endothelial cells in the progression of atherosclerosis in female mice. - Avigail Ehrlich; Graziano Pelli; Bernard Foglia; Filippo Molica; Brenda R Kwak (PLoS ONE)
Atherosclerosis is a progressive arterial disease arising from imbalanced lipid metabolism and a maladaptive immune response. The lymphatic system ensures tissue fluid homeostasis, absorption of dietary fats and trafficking of immune cells to draining lymph nodes, thereby potentially affecting atherogenesis. Endothelial cell-specific deletion of Pannexin1 (Panx1) in apolipoprotein E-deficient (Apoe-/-) mice increased atherosclerosis, suggesting a protective role for Panx1 channels in arterial endothelial function. Here, we investigated the role of Panx1 in lymphatic endothelial cells (LECs) in the initiation and the progression of atherosclerosis. Male or female Prox1-CreERT2+Panx1fl/flApoe-/- and Panx1fl/flApoe-/- mice were fed a high cholesterol diet (HCD) for 6 or 10 weeks. Tamoxifen-induced deletion of Panx1 was performed before or after 4 weeks of HCD. Body weight and serum lipid profiles were determined. The atherosclerotic plaque burden was assessed by Sudan-IV staining on thoracic-abdominal aortas and in aortic roots. Plaque composition was determined by immunohistochemistry. No differences in serum cholesterol, LDL and HDL were observed between genotypes and between sexes after HCD. Bodyweight, serum triglycerides and free fatty acid levels were higher before and after 6 weeks of HCD in male Prox1-CreERT2+Panx1fl/flApoe-/- and control Panx1fl/flApoe-/- mice compared to females of the same genotypes, which was associated with more lipids and inflammatory cells in their atherosclerotic plaques. In contrast, the atherosclerotic plaque burden was higher in female mice. The progression of atherosclerosis in male mice was not different between genotypes. However, female Prox1-CreERT2+Panx1fl/flApoe-/- mice showed enhanced progression of atherosclerosis compared to Panx1fl/flApoe-/- controls of the same sex. In addition, atherosclerotic lesions in female, but not in male, Prox1-CreERT2+Panx1fl/flApoe-/- mice showed T cell enrichment. Altogether, our results reveal differential sex-dependent effects of Panx1 in lymphatic endothelium on the progression of atherosclerosis.